Learning Design for Combinatorics with Realistic Mathematics Education (RME) Approach - Dona Fitriawan; Nurfadilah Siregar; Endar Sulistyowati (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
The purpose of this research is to design learning combinatorics sub-material faktorial, permutation, combination and chance with RME approach. This research is a qualitative research. With this research method using design research. The research techniques used are measurement techniques, direct observation and documentation with tools in the form of objective tests, observation sheets and document sheets. The research subjects were 2 classes, namely A1 and A2 classes in the Mathematical Statistics course, especially combinatorics material totaling 35 students with the learning trajectory in the form of numbers that were applied alternately to students. The conclusion of this research is obtained: 1) in the faktorial sub-material, students are introduced to the RME approach that 4!=24, 3!=6, 2!=2, 1!=1until it is proven that 1!=1; 2) in the permutation and combination sub-material, students are directed to be examples of the same numbers and letters that form the rules of permutation and combination; 3) in the opportunity sub-material, students are exemplified about coins and dice, both in one, two, and three pieces in the context of the problem.